Pengembangan Aplikasi Healthcare Intelligence System Untuk Pemantauan Kesehatan Ibu Dan Anak: Perancangan Aplikasi Frontend - Muhammad Aliffiro Naufal; Ahmad Muklason (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Health is a very important sector and gets great attention by the Government. This sector has the potential to be integrated with information technology. One of the health programs that have been established by the Government is the Maternal and Child Health Program (KIA). The program includes services and care for pregnant women, maternity mothers, breastfeeding mothers, infants and toddlers to preschoolers. However, in the implementation of the program there are several weaknesses, including the implementation process which is still manual using the MCH handbook which makes the process less effective and efficient. Whereas the implementation of the program can be maximized by the use of information technology, including the help of applications. There are many previous studies that try to overcome this problem by making applications. However, of all these applications only focus on aspects of infant growth and the provision of information about maternal and child health. In fact, there are other aspects that also need to be considered related to maternal and child health monitoring. These aspects include aspects of infant development. Infant development is an important factor in assessing deviations in child development. In addition, these various applications have not yet been combined with an intelligent system or Intelligence System to become a Healthcare Intelligence System, for example with an early warning feature related to maternal and child health in case of irregularities. So that the use of information technology can be optimally implemented for monitoring the health of mothers and children. However, in making the Healthcare Intelligence System, input data is needed which will later be processed using algorithms and the features in it. Therefore, it is important to first create an application that contains a data input module for data related to maternal and child health monitoring, from aspects of growth to development. In developing the application, the Waterfall Software Development Life Cycle method is used. The focus of this research is to create a frontend application. The application prototype testing process is carried out using the Usability Testing method to ensure the resulting application is in accordance with the needs. The results obtained from this study are the Healthcare Intelligence System frontend application that has been carried out by Blackbox Testing. This frontend application has been adjusted to the data and parameters contained in the application prototype. This frontend application has also been integrated with the backend application with an API that has been created. With this system designed, both mothers and midwives can take notes to see the health conditions of mothers and children.